Rekonstruksi Konsep Keadilan Distributif dalam Membangun Kesejahteraan Sosial Perspektif Ekonomi Islam - Maulana Ira (Program Studi Hukum Ekonomi Syariah, 2026)
Injustice and inequality in the distribution of income and wealth, both in developed and developing countries that embrace capitalism in their economic systems, create poverty. This study aims to analyze the dynamics of distribution within a capitalist economic system, the nature of distribution within Islamic economics, and Islamic solutions for the government to create prosperity and distributive justice. The method used is a qualitative approach using literature studies from scientific journals, books, and other sources related to Islamic economics. The results of the study indicate that the dynamics of distribution within a capitalist economic system are determined by market mechanisms (prices), private ownership (capital), and free competition. Distributive justice in Islamic economics focuses on the fact that existing economic theories are unable to address the problems of poverty and income and wealth inequality. In achieving distributive justice, Islamic economics requires the government to play a role in upholding values ​​and morals, maintaining the technical operation of market mechanisms, and taking responsibility for market failures.